Pelatihan Penguatan Literasi Teks Sastra bagi Guru di SMA UII Yogyakarta: indonesia - Nurhidayah, Nurhidayah; mawaidi, mawaidi; Kumalasari, Mei Anjar; Suroso, Suroso; Nurhadi, Nurhadi (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
In efforts to develop students’ literacy skills at school, teachers and schools have an important role. With the high quality of teacher literacy in schools, teachers will have broad insight to design literacy learning that encourages students to have the ability to think critically, through understanding, using, evaluating, reflecting on various types of texts to solve problems, and developing individual capacity so they can contribute productively. to society. This Community Service Program with the topic Strengthening Literacy in Literary Texts was carried out at SMA UII Yogyakarta. The method of this service is training and workshops. In addition, adult education methods (andragogy) are also applied using a process approach model. The program implemented is in the form of training. First, "Literary Literacy Insights"; second, "Writing Training"; third, "Writing Assistance"; fourth, "Finalization of Written Products", and fifth "Publishing Works". Through this teacher training, it is hoped that students can be formed who are not only academically intelligent, but also have intellectual depth, emotional sensitivity and a deep understanding of human values.